1994
DOI: 10.1108/02651339410069236
|View full text |Cite
|
Sign up to set email alerts
|

Research Note

Abstract: The cost and data‐gathering problems associated with research in developing countries can be partially remedied by using students as surrogates of other populations. Reports the findings of two studies which investigated the efficacy of students as surrogates of adults in Saudi Arabia. One of these studies was in the domain of attitudes towards advertising and the other in the area of country‐of‐origin effects. Results of the studies suggest that the use of students is appropriate in modelling attitude‐behavio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0
1

Year Published

2006
2006
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 85 publications
(5 citation statements)
references
References 28 publications
0
4
0
1
Order By: Relevance
“…The use of convenience sampling is warranted given the difficulty of random sampling not only in Egypt but also in the Arab region as a whole. Researchers have outlined difficulties in conducting research in crosscultural research in general, and Arab societies in specific, including -among other things -methodological issues, research costs, and funding issues, data-gathering complications, cultures which are not supportive or not familiar with research studies, and weak links between the research community and business sectors (Ali, 1987;Malhotra et al, 1996;Yavas, 1987Yavas, , 1994Yavas and Habib, 1986). The main criterion for inclusion in the survey was that the respondent was an Egyptian with some high school education and at least 1 year of work experience.…”
Section: Data Collectionmentioning
confidence: 99%
“…The use of convenience sampling is warranted given the difficulty of random sampling not only in Egypt but also in the Arab region as a whole. Researchers have outlined difficulties in conducting research in crosscultural research in general, and Arab societies in specific, including -among other things -methodological issues, research costs, and funding issues, data-gathering complications, cultures which are not supportive or not familiar with research studies, and weak links between the research community and business sectors (Ali, 1987;Malhotra et al, 1996;Yavas, 1987Yavas, , 1994Yavas and Habib, 1986). The main criterion for inclusion in the survey was that the respondent was an Egyptian with some high school education and at least 1 year of work experience.…”
Section: Data Collectionmentioning
confidence: 99%
“…In this study, student subjects were used in a laboratory experiment. And even though there is evidence showing that students and managers make similar decisions (eg, Ashton and Kramer, 1980;Mowen and Mowen, 1986;Yavas, 1994), replication of the findings using decision makers in real-life decision-making situations would be desirable.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, consumer behavior studies have indicated that students and nonstudents exhibit similar behavior. In fact, students can effectively substitute for nonstudents or adults in various empirical studies, as demonstrated by Yavas (1994) and Lichtenstein and Burton (1989). Respondents were initially tasked with identifying the top 3 e-commerce websites they most frequently use, providing their domain names.…”
Section: Methodsmentioning
confidence: 99%